Pengaruh Pemandangan dan Material Alam pada Rawat Inap Terhadap Kecemasan Ibu Hamil - Wangsadiputri, Shelvie Kania Hani Gamas; Maharani, Yuni (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2024)
During the pregnancy process, pregnant women often experience anxiety disorders which have a negative impact on personal mental health and fetal health, anxiety that occurs can increase approaching labour. Inpatient room is the patient's closest environment during labor and postpartum which affects anxiety in pregnant women. The use of natural scenery and material in inpatient room is believed able to affect the level of anxiety. The purpose of this study was to determine the effect of the application of natural scenery and natural material in hospital inpatient room on the psychological effects of anxiety felt by pregnant women. This research uses quantitative methods with experiments and literature studies related to the topic of discussion. The results of this study indicate that there is a significant positive effect on the natural scenery and natural material on the anxiety of pregnant women, and the results show that the elements of a real natural scenery are the elements that have the most positive influence on the anxiety of pregnant women. This research is expected to be a reference for designing inpatient rooms by considering the use of natural scenery and natural material and their psychological effects on the anxiety of pregnant women.